Organizational and legal conditions for the creation of sports arbitration in Ukraine - Marina Sannikova (Слобожанський науково-спортивний вісник, 2019)
Purpose: to determine the organizational and managerial conditions for creating sports arbitration in Ukraine. Material & Methods: method of theoretical analysis and generalization of literary sources, which made it possible to determine the state of study of the problem under study; method for analyzing documentary materials, which made it possible to characterize the problem field of creating sports arbitration in Ukraine; method of historicism, which allowed to consider the emergence and characteristics of sports arbitration; methods of analogy of the studied laws and system analysis allowed creating a theoretical basis for substantiating the organizational and legal conditions for creating sports arbitration in Ukraine. Results: the organizational and legal conditions for creating sports arbitration in Ukraine were determined and substantiated, in particular: the place of sports arbitration in the judicial system, the form of activity, legal status, roles, advantages, regulatory framework, founder, name of sports arbitration, and others. Conclusions: it was found that the creation of a single sports arbitration, whose competence will include the resolution of various conflicts relating to the sphere of physical culture and sports, is an urgent need. It has been established that for the qualified resolution of sports disputes, we need both lawyers specializing in the field of sports legal support, as well as sports officials, managers, coaches, that is, specialists who are well-versed in the field of physical culture and sports.